2017
DOI: 10.1097/hrp.0000000000000149
|View full text |Cite
|
Sign up to set email alerts
|

Scope, Scale, and Dose of the World’s Largest School-Based Mental Health Programs

Abstract: Untreated mental health problems are among the most disabling, persistent, and costly health conditions. Because they often begin in childhood and continue into adulthood, there has been growing interest in preventive mental health programs for children. In recent years, several such programs have been implemented at regional, state, or national scale, and although many experimental studies have documented positive outcomes of individual programs, this article represents the first attempt to systematically com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
42
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 45 publications
1
42
1
3
Order By: Relevance
“…Our finding is also in agreement with the report of Ashenafi et al [41] that the most diagnosed mental health disorder in their study was anxiety disorder. However, it contrasts with the report of Tunde-Ayinmode [36] in South West Nigeria who found schizophrenia as the most common mental health disorder in his study. It also contrasts with report of Lawrence et al [43], who found ADHD as the most common mental health disorder amongst Australian school children.…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…Our finding is also in agreement with the report of Ashenafi et al [41] that the most diagnosed mental health disorder in their study was anxiety disorder. However, it contrasts with the report of Tunde-Ayinmode [36] in South West Nigeria who found schizophrenia as the most common mental health disorder in his study. It also contrasts with report of Lawrence et al [43], who found ADHD as the most common mental health disorder amongst Australian school children.…”
Section: Discussioncontrasting
confidence: 97%
“…The developed world realizing the importance of sound mental health in the development of children and adolescents, organized several school-based mental health interventions geared towards mental health promotion or primary prevention for all students in school [35]. Available researches have shown moderate to strong evidence that these interventions are effective in promoting good mental health and related outcomes among school children [36]. Research has also demonstrated that students who receive social, emotional and mental health support achieve better academically, because the school climate, classroom behaviour, on-task learning and students' sense of connectedness and well-being tend to improve [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Others would reserve this term for broader programmes that worked at universal, targeted and indicated levels of prevention simultaneously, which often include a mixture of environment, didactic and individualised content. 130,131 The training of a critical mass of school staff in IY TCM shows promise. A quasi-experimental Norwegian evaluation matched 21 schools in which all Grade 1-3 teachers (children aged 6-8 years) were trained with 22 matched schools that did not receive training.…”
Section: Discussionmentioning
confidence: 99%
“…The aims of MTSS are to prevent and ameliorate MH problems while promoting social, emotional, and academic success among all individuals in a school . Although a robust evidence base exists for the effectiveness of singular school‐based prevention and intervention programs, little evidence is available to support the feasibility and effectiveness of MTSS models in “real world settings” that embed a continuum of whole‐school and classroom‐level prevention and early intervention programs alongside small group and individual services for selected youth.…”
mentioning
confidence: 99%